A qualitative and quantitative account of patient's experiences of ketamine and its antidepressant properties. (August 2021) - Sumner, Rachael L; Chacko, Emme; McMillan, Rebecca; Spriggs, Meg J; Anderson, Christie; Chen, James; French, Amelia; Jung, SungHun; Rajan, Akshaya; Malpas, Gemma; Hay, John; Ponton, Rhys; et al.
Background: Ketamine is central to one of the most rapidly growing areas of neuroscientific research into novel treatments for depression. Limited research has indicated that the psychedelic properties of ketamine may play a role in its antidepressant effects. Aim: The aim of the current study was to explore the psychedelic experiences and sustained impact of ketamine in major depressive disorder. Methods: In the current study, ketamine (0.44 mg/kg) was administered to 32 volunteers with major depressive disorder in a crossover design with the active-placebo remifentanil, in a magnetic resonance imaging (MRI) environment. The 11-dimension altered states of consciousness questionnaire and individual qualitative interviews were used to capture the acute psychedelic experience. The Montgomery-Asberg Depression Rating Scale and further interviewing explored lasting effects. The second qualitative interview took place ⩾3 weeks post-ketamine. Results: Greater antidepressant response (reduction in Montgomery-Asberg Depression Rating Scale at 24 h) correlated with the 11-dimension altered states of consciousness dimensions: spirituality, experience of unity, and insight. The first qualitative interview revealed that all participants experienced perceptual changes. Additional themes emerged including loss of control and emotional and mood changes. The final interview showed evidence of a psychedelic afterglow, and changes to perspective on life, people, and problems, as well as changes to how participants felt about their depression and treatments. Conclusions: The current study provides preliminary evidence for a role of the psychedelic experience and afterglow in ketamine's antidepressant properties. Reflexive thematic analysis provided a wealth of information on participants' experience of the study and demonstrated the psychedelic properties of ketamine are not fully captured by commonly used questionnaires.